Cluster analysis in Higher Education Institutions' knowledge identification and production processes (2022)
The objective of this study is to describe the processes of identification and creation of knowledge in higher education institutions (HEI). The sample is composed of 7 universities in the city of Barranquila in Colombia, and is non-probabilistic. For this purpose, a survey was used to collect data from the directors and vice-rectors of research of the research departments. For its part, the research methodology is framed in the tools of cluster analysis and principal component analysis. The established approach made it possible to demonstrate that universities have two characteristics for identifying and creating knowledge in HEIs: community learning and individual learning. © 2022 The Authors. Published by Elsevier B.V. This is an open access article under the CC BY-NC-ND license (https://creativecommons.org/licenses/by-nc-nd/4.0) Peer-review under responsibility of the Conference Program Chairs.